Posterior Fossa Tumours Presenting to Psychiatrists - M. F. Bristow (Behavioural Neurology)
Posterior fossa tumours may in their early stages give rise to dizziness, nausea and subjective unsteadiness. Such symptoms are commonly accompanied by psychological distress and are not always easy to diagnose. In the presence of a past psychiatric history, they may be wrongly interpreted as exacerbations of neurotic disorder. Two examples of this are given. Because of the commonness of vestibular symptoms and the rapid growth of these tumours, a normal scan early in the history may be misleading.